Kebijakan sensorship di perpustakaan sekolah - Fatmawati, Siti; Nugrahaningtyas, Octarina; Paramita, Puspa (2018)
Paperinimembahastentangkebijakansensorshipdiperpustakaansekolah.PerpustakaansekolahdisinimeliputitingkatSDSMPdanSMA.Sensorshipdiartikansebagailaranganuntukmemproduksimeyebarluaskanataumenjualbahanyangberbahayaatautidakpantasuntukdisebarluaskan.Kegiatansensorshippentingdilakukandiperpustakaansekolahagarmemastikankoleksibahanpustakaamanpositifdansesuaiuntukdibacaolehsiswa.Kegiatansensorshiptidakhanyadilakukanolehpustakawandangurunamunorangtua/waliberhakmenyumbangkanpendapatnya.Hasilmenunjukkanbahwakebijakansensorshippadaperpustakaansekolahkebanyakanbelumsecarajelastertulis.Beberapahalyangperludiperphatikandalampenyensoranyaknikrtiteriakoleksiyangakandiosensorprosespenyensorandankendalayangmungkindialamipustsawanpadasaatpenyensoran.Dalampaperinikamimenggunakanmetodepeneletianstudiliteraturdenganpendekatankualitatif.KataKuncisensorshippenyensoranbukuperpustakaansekolahkoleksiperpustakaan